A Preliminary Experimental Examination of the Effect of Emotion Dysregulation and Impulsivity on Risky Behaviors among Women with Sexual Assault-Related Posttraumatic Stress Disorder - Weiss, Nicole H. (Behav Modif, 2014)
Posttraumatic stress disorder (PTSD) is associated with a wide range of risky behaviors (e.g., substance use and risky sexual behaviors); however, few studies have examined mechanisms that may underlie risky behaviors in this population. The present study utilized a prospective experimental design to examine the effects of emotion dysregulation and impulsivity on risky behaviors across time. Thirty women with sexual assault-related PTSD were randomly assigned to receive emotion modulation, impulsivity reduction, or healthy living (comparison condition) skills trainings. Participants completed measures of emotion dysregulation, impulsivity, and risky behaviors pre-manipulation and one month post-manipulation. Participants in the emotion modulation and impulsivity reduction conditions reported a significant reduction in risky behaviors from pre- to post-manipulation relative to the healthy living condition. Changes in emotion dysregulation from pre- to post-manipulation fully accounted for reductions in risky behaviors over time. Results provide preliminary experimental support for the role of emotion dysregulation in risky behaviors.